Orientation Ordering and Chiral Superstructures in Fullerene Monolayer on Cd (0001) - Shang, Yuzhi (Nanomaterials (Basel), 2020)
The structure of C(60) thin films grown on Cd (0001) surface has been investigated from submonolayer to second monolayer regimes with a low-temperature scanning tunneling microscopy (STM). There are different C(60) domains with various misorientation angles relative to the lattice directions of Cd (0001). In the (2√3 × 2√3) R30° domain, orientational disorder of the individual C(60) molecules with either pentagon, hexagon, or 6:6 bond facing up has been observed. However, orientation ordering appeared in the R26° domain such that all the C(60) molecules adopt the same orientation with the 6:6 bond facing up. In particular, complex chiral motifs composed of seven C(60) molecules with clockwise or anticlockwise handedness have been observed in the R4° and R8° domains, respectively. Scanning tunneling spectroscopy (STS) measurements reveal a reduced HOMO–LOMO gap of 2.1 eV for the C(60) molecules adsorbed on Cd (0001) due to the substrate screening and charge transfer from Cd to C(60) molecules.